Vitamin K prophylaxis and vitamin K deficiency bleeding in the UK. (29th September 2015) - Busfield, A; Samuel, R; McNinch, A; Tripp, J
Abstract : Aim: To correlate incidence, morbidity and mortality of vitamin K deficiency bleeding (VKDB) with changing practices in vitamin K (VK) prophylaxis in the UK—most recently the withdrawal of Konakion Neonatal in 2006, leaving Konakion MM as the only licenced preparation for prophylaxis in the UK. Method: Since 1988 four 2-year studies of VKDB have been undertaken via the British Paediatric Surveillance Unit (BPSU), each with a contemporaneous survey of VK prophylaxis. The 2001–2002 survey preceded withdrawal of Konakion Neonatal, the 2006–2008 survey followed it. Results: VKDB incidences in the two recent studies are not statistically different, but lower than previously. VK was recommended by all units in the two recent studies. In 1993–1994 only 38% of babies received intramuscular VK. By 2001–2002, 60% of units recommended intramuscular, most using Konakion Neonatal; by 2006–2008 72% of units recommended intramuscular, all using Konakion MM. In 1993–1994, 60% of babies were routinely offered oral prophylaxis, ending by day 7 in 25% of these. In 2001–2002 and 2006–2008 almost all used multiple-dose regimens extending to 28+ days in breastfed infants. Some parents withhold consent for any VK prophylaxis (50% of recent cases). The three cases of late VKDB associated with liver disease in 2006–2008 were jaundiced at presentation on day 23, 66 and 86; the first had oral, the others intramuscular VK. Long-term sequelae from intracranial haemorrhage are expected in one; another died of liver failure. Investigating prolonged jaundice was not routine in 10% of units responding (n=198 of total 236 units) Conclusions: ▸ Most babies developing VKDB are breast-fed and have received no VK, usually because parents refuse it. Some 30% have unrecognised liver disease. ▸ Substituting Konakion MM for Konakion Neonatal has not been associated with a significant increase in VKDB incidence. ▸ Prophylaxis cannot alone prevent all cases. Early detection of liver disease by investigating prolonged jaundice identifies some of the most vulnerable babies before they bleed and may improve the prognosis of the underlying disease; all units should promote this practice.